Herpes Zoster in Children and Adolescents: Case Series Of 8 Patients - Nair, Pragya A; Patel, Pankil H (National Journal of Community Medicine, 2013)
Herpes zoster can occur at any age but is rare in childhood and adolescents. Zoster can occur at any time after primary varicella infection or varicella vaccination. Recent studies have shown its increasing incidence in children. Maternal varicella infection during pregnancy and varicella occurring in the newborn represent risk factors for childhood herpes zoster. As varicella vaccine is a live attenuated virus, herpes zoster can develop in a vaccine recipient, but its incidence is less than natural infection. It is usually diagnosed clinically as unilateral vesicular eruption following a dermatome or dermatomes. Zoster in children is frequently mild, post herpatic neuralgia occurs rarely if ever. We present eight cases of zoster in children and adolescents.